2022
DOI: 10.3390/v14020432
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-Based Antiviral Innate Immunity in Plants

Abstract: Multiple antiviral immunities were developed to defend against viral infection in hosts. RNA interference (RNAi)-based antiviral innate immunity is evolutionarily conserved in eukaryotes and plays a vital role against all types of viruses. During the arms race between the host and virus, many viruses evolve viral suppressors of RNA silencing (VSRs) to inhibit antiviral innate immunity. Here, we reviewed the mechanism at different stages in RNAi-based antiviral innate immunity in plants and the counteractions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 202 publications
0
19
0
Order By: Relevance
“…In plants, it has been shown that RNA silencing is a crucial immune system to preventing viral infections ( Yang and Li, 2018 ; Li et al, 2019 ; Jin et al, 2021 , 2022 ). To overcome the host immune system, plant viruses have developed various VSRs to inhibit RNA silencing at different steps ( Feng et al, 2018 ; Guo et al, 2019 ; Jin et al, 2021 , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In plants, it has been shown that RNA silencing is a crucial immune system to preventing viral infections ( Yang and Li, 2018 ; Li et al, 2019 ; Jin et al, 2021 , 2022 ). To overcome the host immune system, plant viruses have developed various VSRs to inhibit RNA silencing at different steps ( Feng et al, 2018 ; Guo et al, 2019 ; Jin et al, 2021 , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, it has been shown that RNA silencing is a crucial immune system to preventing viral infections ( Yang and Li, 2018 ; Li et al, 2019 ; Jin et al, 2021 , 2022 ). To overcome the host immune system, plant viruses have developed various VSRs to inhibit RNA silencing at different steps ( Feng et al, 2018 ; Guo et al, 2019 ; Jin et al, 2021 , 2022 ). Previous studies have shown that the most common counteraction of VSRs is to suppress vsiRNA amplification ( Guo et al, 2019 ; Li and Wang, 2019 ; Jin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations